HEGEMONI DALAM KUMPULAN CERPEN TEH DAN PENGKHIANAT KARYA IKSAKA BANU - Budiman, Putra Ariq; Suhardi , Imam; Nani Hari Yanti, Sri (Hasta Wiyata, 2024)
This research discusses the aspect of hegemony in the short story collection "Teh dan Pengkhianat" by Iksaka Banu. The purpose of this study is to describe the characters, plot, and setting, as well as to describe the domination and hegemony in the short story collection "Teh dan Pengkhianat" by Iksaka Banu. Methodologically, a qualitative descriptive approach is used, while theoretically using a literary sociology approach. The collected data is then analyzed to assess and identify the aspects of Antonio Gramsci's hegemony in the short story collection "Teh dan Pengkhianat" by Iksaka Banu. The analysis result of "Hegemony in the Short Story Collection 'Teh dan Pengkhianat' by Iksaka Banu" shows the existence of total hegemony, declining hegemony, and minimum hegemony imposed by the Dutch on the natives as an effort to perpetuate their power in the Dutch East Indies. The aspect of hegemony can be seen from the ideas, storyline, narrative, and dialogue conveyed by the characters in the short stories "Sebutir Peluru Saja" and "Di Atas Kereta Angin". Hegemony in this short story collection can be identified through structural analysis which includes characters and characterization, plot, setting, time setting, and social setting.